The influence of environmental and non-environmental factors on the development of settlement in a mountain catchment - Witkowski Karol; Witkowski Marcin (Miscellanea Geographica: Regional Studies on Development, 2024)
Settlement in the Skawa catchment (Polish Western Carpathians) developed between the 7th and 18th centuries, influenced by political, economic and natural factors. Up to the 14th century, natural factors dominated, related to the location of settlements. Later, with changes in the borders of the Polish Kingdom, new settlements were established much faster in order to expand the Polish and Silesian influence. From the 15th century, the higher parts of the Beskids were intensively settled with the clearing of the Carpathian primeval forest. This stage of colonization took place with the participation of the Wallachian population. On the scale of the entire catchment area, the tendency of the settlements to spread up the main river is typical for mountainous areas. However, in the case of several settlements, their location was dictated by political factors, which disturbs this picture.